Pentosan polysulfate decreases myocardial expression of the extracellular matrix enzyme ADAMTS4 and improves cardiac function in vivo in rats subjected to pressure overload by aortic banding. - Maria Vistnes; Jan Magnus Aronsen; Ida G Lunde; Ivar Sjaastad; Cathrine R Carlson; Geir Christensen (PLoS ONE)
Background We hypothesized that cleavage of the extracellular matrix (ECM) proteoglycans versican and aggrecan by ADAMTS (a disintegrin and metalloprotease with thrombospondin motifs) proteases, which contributes to stress-induced ECM-reorganization in atherogenesis and osteoarthritis, also play a role in heart failure development. Objectives The primary objective was to identify alterations in expression of ADAMTS versicanases and aggrecanases during development of heart failure, while evaluation of the effects of in vivo modulation of relevant changes in ADAMTS activity constituted the secondary objective. Methods Myocardial levels of versican, aggrecan, and their ADAMTS cleaving proteases were examined in Wistar rats six weeks after aortic banding (AB), and versican and selected ADAMTS versicanases were further analyzed in neonatal cardiomyocytes (NCM) and cardiac fibroblasts (NFB) after stimulation by inflammatory mediators. Based on the initial findings, ADAMTS4 was selected the most promising therapeutic target. Thus, rats with AB were treated with pentosan polysulfate (PPS), a polysaccharide with known ADAMTS4-inhibitory properties, and effects on versican fragmentation, left ventricular function and geometry were evaluated. Results We discovered that myocardial mRNA and protein levels of ADAMTS1 and -4, and mRNA levels of versican, aggrecan, and ADAMTS8 increased after AB, and TNF-α and IL-1β synergistically increased mRNA of versican and ADAMTS4 in NCM and NFB and secretion of ADAMTS4 from NCM. Furthermore, PPS-treatment improved systolic function, demonstrated by an improved fractional shortening (vehicle 48±3% versus PPS 60±1%, p<0.01) after AB. Following PPS-treatment, we observed an ∼80% reduction in myocardial ADAMTS4 mRNA (p = 0.03), and ∼50% reduction in the extracellular amount of the p150 versican fragments (p = 0.05), suggesting reduced versicanase activity. Conclusions Our findings suggest that AB induces an increase in myocardial ADAMTS4 versicanase activity, and that PPS-treatment improved systolic function in the pressure-overloaded heart, holding promise as a novel therapeutic agent in heart failure.